MODERN VIEWS ON MORPHOLOGICAL CHANGES IN THE CEREBRAL CORTEX IN PATIENTS IN THE POSTCOVID PERIOD (World Bulletin of Public Health, 2024)
Coronavirus infection (COVID-19) has spread worldwide since the coronavirus was detected in December 2019 and has caused the deaths of millions. The new coronavirus infection (COVID-19) poses a serious public health problem. As of April 2021, since the beginning of the pandemic, the World Health Organization has registered about 3 million deaths from a new coronavirus infection caused by the SARS-CoV-2 virus in humans
Keywords: Cortex; brain; morphology